2022
DOI: 10.3389/fmed.2022.1042706
|View full text |Cite
|
Sign up to set email alerts
|

PET image enhancement using artificial intelligence for better characterization of epilepsy lesions

Abstract: Introduction[18F]fluorodeoxyglucose ([18F]FDG) brain PET is used clinically to detect small areas of decreased uptake associated with epileptogenic lesions, e.g., Focal Cortical Dysplasias (FCD) but its performance is limited due to spatial resolution and low contrast. We aimed to develop a deep learning-based PET image enhancement method using simulated PET to improve lesion visualization.MethodsWe created 210 numerical brain phantoms (MRI segmented into 9 regions) and assigned 10 different plausible activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 62 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Due to the presence of local hyperintensities in some FCD cases, some detection models [ 14 , 15 ] added FLAIR sequences to improve model performance. In addition, Flaus et al [ 26 ] proposed a deep learning-based PET image enhancement method using simulated PET to improve lesion visualization, from 38 to 75%, in a 37-case adult cohort. Although the combination of multiple imaging techniques would benefit the subtle FCD detection [ 27 ], we aim to simplify input requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the presence of local hyperintensities in some FCD cases, some detection models [ 14 , 15 ] added FLAIR sequences to improve model performance. In addition, Flaus et al [ 26 ] proposed a deep learning-based PET image enhancement method using simulated PET to improve lesion visualization, from 38 to 75%, in a 37-case adult cohort. Although the combination of multiple imaging techniques would benefit the subtle FCD detection [ 27 ], we aim to simplify input requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Folego et al ( 2020 ) have adapted LeNet, VGGNet, GoogLeNet, and ResNet in 3D domain to the aim of AD detection. Flaus et al ( 2022 ) has proposed a 3D sequential ResNet to enhance PET images for better visualization of brain lesions. A transparent CNN framework proposed by Eitel et al ( 2019 ) has revealed the decision process of CNN in the diagnosis of MS and pointed out more disease-relevant features in MR images.…”
Section: Introductionmentioning
confidence: 99%
“…They are mainly based on auto‐encoders, using latent space representation of the FDG normal distribution to detect out‐of‐distribution areas that could correspond to the EZ 16,27,28 . Other approaches are based on image synthesis: to predict enhanced [ 18 F]FDG PET image to facilitate visual analysis 29 or to predict the FDG normal distribution from a T1w image of the patient and compare it to the actual clinical PET. Proofs of concept of clinical relevance of last approach have been published in dementia 30 and epilepsy 25 .…”
Section: Introductionmentioning
confidence: 99%